Method for acquiring and analyzing porosity test data of battery pole piece made of ternary positive electrode material
By conducting porosity tests on the ternary positive electrode material battery pole sheets, calculating the deviation rate and establishing a fitting relationship curve, the problem of incomparable porosity data between different battery factories and suppliers is solved, and standardized control of the battery production process is achieved.
Patent Information
- Application Number
- CN202510219535.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-05-16
AI Technical Summary
Different porosity testing instruments are used between different battery manufacturers and suppliers, resulting in the porosity data of battery raw materials being incomparable, affecting the standardized control of the battery production process.
By preparing multiple ternary positive electrode materials, porosity tests are performed using mercury insulators and true density meters respectively, the deviation rate between the obtained test data is calculated, and a quadratic polynomial fitting relationship curve with the deviation rate varies with specific process parameters is established to provide the basis for the conversion of the porosity test data.
This realizes the indiscriminate comparison analysis of porosity test data between different test instruments, and improves the standardized management and control capabilities in the battery production process.
Smart Images

Figure CN120009147A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for acquiring and analyzing test data of the porosity of a battery electrode sheet of a ternary positive electrode material. Background Art
[0002] The porosity of battery pole pieces is an important parameter in the design and manufacturing process of lithium-ion batteries, which is closely related to the rate performance, internal resistance and cycle life of the battery. The porosity of battery pole pieces is generally tested using a mercury intrusion tester and a true density tester.
[0003] The mercury intrusion porosimeter is based on the fact that mercury is non-wettable to most solid materials. After the solid material is placed in the mercury intrusion porosimeter, the applied external pressure is gradually increased to allow the mercury to gradually enter the pores of the solid material. By measuring the amount of mercury entering the pores under different external pressures, the porosity, pore size distribution and other parameters of the solid material can be calculated. However, due to the high cost of the mercury intrusion porosimeter and the highly toxic mercury metal used in the mercury intrusion porosimeter, it is easy to volatilize into mercury vapor during the test, which poses a potential hazard to the health of the tester.
[0004] The true density meter is to put the solid material into a closed container, then introduce inert gas to replace the air around and inside the solid material, and use Bohr's law to calculate the real volume of the solid material, so as to calculate the true density of the solid material (i.e. the density excluding pores) according to the mass of the solid material, and then combine the apparent density of the solid material (i.e. the density including pores) measured by the existing apparent density test methods such as drainage method to calculate the porosity of the solid material. The inert gas used by the true density meter is non-toxic and harmless, and has the advantages of low testing cost.
[0005] During the battery production process, when suppliers supply battery raw materials to different battery factories, the battery factories usually conduct relevant performance tests on the battery raw materials, such as porosity tests, to verify whether the battery raw materials supplied by the supplier meet the procurement requirements. However, the porosity testing instruments used by suppliers and different battery factories are different, which will lead to differences in the porosity data of the battery raw materials provided by the supplier and the porosity data obtained by the battery factory test, making it impossible to form an effective analysis and comparison, which seriously affects the standardized control of the battery production process.
[0006] When conducting competitive product analysis or communicating battery electrode production processes between different companies in the industry, the data obtained through different testing equipment and testing methods are usually not comparable. Summary of the invention
[0007] The present application provides a method for acquiring and analyzing test data of the porosity of a battery electrode based on a ternary positive electrode material, which can provide a basis for conversion of different test results obtained when the porosity of the battery electrode is tested using a mercury intrusion tester and a true density tester respectively.
[0008] Specifically, the present application is implemented through the following technical solutions:
[0009] On the one hand, the present application provides a method for obtaining and analyzing the porosity test data of a battery electrode based on a ternary positive electrode material, including:
[0010] Using specific process parameters that affect the porosity of the battery pole piece of the ternary positive electrode material as reference variables, a plurality of battery pole pieces of the ternary positive electrode material are prepared;
[0011] A mercury intrusion instrument is used to sequentially test the porosity of each of the battery pole pieces, and a plurality of first porosity data are obtained by calculation; a true density meter is used to sequentially test the porosity of each of the battery pole pieces, and a plurality of second porosity data are obtained by calculation; and a deviation rate of one of the plurality of first porosity data and the plurality of second porosity data relative to the other is calculated respectively;
[0012] In the same coordinate system, a data scatter plot of the specific process parameter and a data scatter plot of the deviation rate are established, and linear fitting processing is performed on the two data scatter plots to obtain a quadratic polynomial fitting relationship curve about the variation of the deviation rate with the specific process parameter.
[0013] Optionally, before taking the specific process parameters affecting the porosity of the battery electrode sheet of the ternary positive electrode material as the reference variable, the method further includes:
[0014] Using a single variable method to prepare multiple battery pole pieces of ternary positive electrode materials using multiple process parameters that affect the porosity of the battery pole piece, and using a mercury intrusion porosimeter and a true density meter to test the porosity of the battery pole pieces of the multiple ternary positive electrode materials, so as to calculate the mercury intrusion porosity test data and the true density meter porosity test data respectively;
[0015] Establishing a variation trend curve between the porosity test data of the mercury intrusion instrument and each of the process parameters, and a variation trend curve between the porosity test data of the true density instrument and each of the process parameters;
[0016] According to the two change trend curves, the process parameters that show monotonic changes with the porosity test data of the mercury intrusion instrument and the porosity test data of the true density instrument are obtained from all the process parameters as the specific process parameters.
[0017] Optionally, all the process parameters include compaction density, and at least one of the particle size of raw material particles, binder dosage, coating thickness, coating speed and rolling pressure other than the compaction density.
[0018] Optionally, the specific process parameters include compaction density;
[0019] Taking the specific process parameters that affect the porosity of the battery pole piece of the ternary positive electrode material as reference variables, a plurality of battery pole pieces of the ternary positive electrode material are prepared, including:
[0020] The rolling parameters are set according to the preset compaction density range of the battery pole piece of the ternary positive electrode material, and after rolling with different rolling parameters, a plurality of battery pole pieces of the ternary positive electrode material with different compaction densities are obtained.
[0021] Optionally, the quadratic polynomial fitting relationship curve of the deviation rate changing with the compacted density is y=ax 2 +bx+c; wherein, 0<a, b<0, 0<c.
[0022] Optionally, a, b and c simultaneously satisfy: 0<a<1, -2<b<0, 0<c<1.
[0023] Optionally, the fitting degree of the quadratic polynomial fitting relationship curve is greater than or equal to 90%.
[0024] Optionally, the preset compaction density range is greater than or equal to 2.5 g / cm 3 , and less than or equal to 4g / cm 3 .
[0025] Optionally, the ternary positive electrode material includes a ternary positive electrode material containing nickel element.
[0026] Optionally, the number of battery pole pieces of the ternary positive electrode material is greater than or equal to 10.
[0027] The technical solution provided by this application can achieve the following beneficial effects:
[0028] The present application provides a method for acquiring and analyzing porosity test data of battery pole pieces based on ternary positive electrode materials. First, a plurality of battery pole pieces of ternary positive electrode materials are prepared using specific process parameters as reference variables. Then, the porosity test data are respectively tested and calculated using a mercury porosimeter and a true density meter, and the deviation rate between the two is calculated. Then, a quadratic polynomial fitting relationship curve of the deviation rate varying with specific process parameters is obtained by a linear fitting method. The fitting relationship curve can be used to provide an effective conversion basis for the porosity test data when the test instrument is replaced between the mercury porosimeter and the true density meter, so as to realize the indifferent comparative analysis of the test data obtained by the porosity test using different test instruments, which is beneficial to the standardized control in the battery production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a flow chart of a method for acquiring and analyzing battery electrode porosity test data shown in an exemplary embodiment of the present application.
[0030] Figure 2 It is another flow chart of a method for acquiring and analyzing battery pole piece porosity test data shown in an exemplary embodiment of the present application.
[0031] Figure 3 This is a graph showing the change in porosity data of a ternary positive electrode material NCM622 battery pole piece at different compaction densities, as shown in an exemplary embodiment of the present application, obtained by using a mercury porosimeter and a true density meter to test them respectively.
[0032] Figure 4 It is a quadratic polynomial fitting relationship curve showing the variation of the deviation rate of the ternary positive electrode material NCM622 battery pole piece with the compaction density shown in an exemplary embodiment of the present application. DETAILED DESCRIPTION
[0033] The technical solution of the present application will be described in detail below in conjunction with the accompanying drawings.
[0034] Here, the technical solutions in the embodiments (or "implementations") of the present application will be described clearly and completely in conjunction with the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements.
[0035] If there are terms involving directional indications or positional relationships in the embodiments of the present application (such as up, down, left, right, front, back, inside, outside, top, bottom, center, vertical, horizontal, longitudinal, transverse, length, width, counterclockwise, clockwise, axial, radial, circumferential, etc.), such terms are only used to explain the relative positional relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings); if the specific posture changes, the directional indication or positional relationship will also change accordingly. In addition, the terms "first", "second", etc. involved in the embodiments of the present application are only used for the purpose of convenience of description and cannot be understood as indicating or implying relative importance.
[0036] Ternary positive electrode materials generally refer to battery positive electrode materials containing three metal elements: nickel (Ni), cobalt (Co), and manganese (Mn). The chemical formula can be expressed as LiNi x Co y Mn z O2, where x+y+z=1, referred to as NCM. This application is mainly aimed at acquiring and processing the porosity test data of battery pole pieces prepared with ternary positive electrode materials.
[0037] See also Figure 1 The present application provides a method for obtaining and analyzing test data of the battery electrode porosity of a ternary positive electrode material, comprising:
[0038] S1. Using specific process parameters that affect the porosity of battery electrodes of ternary positive electrode materials as reference variables, a plurality of battery electrodes of ternary positive electrode materials are prepared.
[0039] S2. Use a mercury porosimeter to test the porosity of each battery electrode in turn, and calculate a plurality of first porosity data; use a true density meter to test the porosity of each battery electrode in turn, and calculate a plurality of second porosity data; respectively calculate the deviation rate of one of the plurality of first porosity data and the plurality of second porosity data relative to the other.
[0040] S3. In the same coordinate system, a data scatter plot of specific process parameters and a data scatter plot of deviation rate are established, and linear fitting processing is performed on the two data scatter plots to obtain a quadratic polynomial fitting relationship curve about the variation of deviation rate with specific process parameters.
[0041] By introducing specific process parameters that affect porosity, the first porosity data obtained by the mercury intrusion test and the second porosity data obtained by the true density test, which were originally difficult to directly quantify, can be converted into data expressed through mathematical formulas. The calculated deviation rate can more intuitively reflect the degree of deviation between different porosity test results. This application obtains a quadratic polynomial fitting relationship curve about the change of deviation rate with specific process parameters through a linear fitting method. The fitting relationship curve can be used to provide an effective conversion basis for porosity test data when the test instrument is replaced between the mercury intrusion tester and the true density tester, so as to realize the horizontal indifferent comparison analysis between the different porosities measured by the true density tester and the mercury intrusion tester for battery pole pieces with ternary positive electrode materials with different compaction densities. When conducting competitive product analysis business, or when communicating battery pole piece production processes between different companies in the industry, the difficulty of data comparison and analysis can also be leveled, thereby achieving indifferent data comparison, which is conducive to standardized control in the battery production process.
[0042] For example, after using a mercury intrusion instrument to test the porosity of each battery pole piece, and using a true density meter to test the porosity of each battery pole piece, if the deviation rate of the second porosity data of each battery pole piece relative to the first porosity data is calculated, then the deviation rate = (second porosity - first porosity) / first porosity × 100%. In this case, the main calculation is the degree to which the second porosity data tested by the true density meter deviates from the first porosity data tested by the mercury intrusion instrument, and the test changes of the true density meter are measured based on the mercury intrusion instrument. For another example, after using a mercury intrusion instrument to test the porosity of each battery pole piece, and using a true density meter to test the porosity of each battery pole piece, if the deviation rate of the first porosity data of each battery pole piece relative to the second porosity data is calculated, then the deviation rate = (first porosity - second porosity) / second porosity × 100%. In this case, the main calculation is the degree of deviation of the first porosity data tested by the mercury intrusion instrument from the second porosity data tested by the true density instrument. The test change of the mercury intrusion instrument is measured based on the true density instrument. The appropriate deviation rate calculation method can be selected according to the specific situation in the actual application.
[0043] It should be noted that the establishment of the data scatter plot and the processing of linear fitting can be performed in a data visualization tool such as but not limited to Excel.
[0044] See also Figure 2 In one embodiment, before taking the specific process parameters affecting the porosity of the battery electrode sheet of the ternary positive electrode material as reference variables, it also includes:
[0045] S01. Using a single variable method to prepare multiple battery pole pieces of ternary positive electrode materials using multiple process parameters that affect the porosity of battery pole pieces, and using a mercury intrusion porosimeter and a true density meter to test the porosity of the battery pole pieces of the multiple ternary positive electrode materials, so as to calculate the mercury intrusion porosity test data and the true density meter porosity test data respectively;
[0046] S02. Establishing a change trend curve between the porosity test data of the mercury intrusion instrument and each process parameter, and a change trend curve between the porosity test data of the true density instrument and each process parameter;
[0047] S03. According to the two change trend curves, the process parameters that show monotonic changes with the porosity test data of the mercury intrusion instrument and the porosity test data of the true density instrument are obtained among all the process parameters as specific process parameters.
[0048] There are two main categories of process parameters that affect the porosity of battery pole pieces, one is material parameters, and the other is process condition parameters. Among them, material parameters include parameters such as particle size and distribution of raw material particles and binder dosage. Process condition parameters include parameters such as particle size of raw material particles, binder dosage, coating thickness, coating speed and rolling pressure. Considering the pursuit of different performances such as fast charging performance and long battery life performance in the battery production process, it is necessary to make different adjustments to the process parameters involved in the production process. However, no matter what process parameters are changed to prepare a battery pole piece that meets actual production needs, the core parameter that can directly affect the porosity of the battery pole piece is the compaction density, while other process parameters indirectly affect the compaction density and then affect the porosity. In other words, the trend of porosity changing with compaction density is monotonically decreasing, that is, the greater the compaction density of the pole piece, the smaller the porosity value. This is because a high compaction density means that the pole piece will be rolled more compactly, the size of the gaps between the material particles in the pole piece will be smaller, and the corresponding pole piece porosity will be lower. However, the porosity does not have obvious monotonic changes with the change trend of other process parameters such as particle size of raw material particles, binder dosage, coating thickness, coating speed and rolling pressure except compaction density. Since the particle size, binder dosage, coating thickness, coating speed and the like of raw material particles are all one of the influencing conditions for controlling compaction density, it is impossible to directly establish a monotonic linear relationship with compaction density, and it is also impossible to establish a monotonic linear relationship with the porosity of the pole piece. For example, the larger the particle size of raw material particles does not mean that the compaction density will be smaller or larger, and it does not mean that the porosity will be larger or smaller. The particle size of raw material particles only plays the role of the flatness of the pole piece in the process of pole piece processing, as a consideration factor in designing the optimal compaction density value of the pole piece. Similarly, the process parameters such as binder dosage, coating thickness, coating speed, etc. are also the same. Therefore, this application finds the changing relationship between each process parameter and porosity, and finally determines the process parameter that changes monotonically with the porosity as a specific process parameter, which is convenient for the subsequent production of a regular fitting relationship curve.
[0049] In one embodiment, all process parameters include compaction density and at least one of particle size of raw material particles, binder dosage, coating thickness, coating speed and roller pressure other than compaction density.
[0050] In one embodiment, the specific process parameters include compaction density. The above step S1 is specifically as follows:
[0051] The rolling parameters are set according to the preset compaction density range of the battery pole piece of the ternary positive electrode material, and a plurality of battery pole pieces of the ternary positive electrode material with different compaction densities are obtained after rolling with different rolling parameters. This facilitates the subsequent establishment of a quadratic polynomial fitting relationship curve of the deviation rate changing with the compaction density.
[0052] The rolling parameters include rolling pressure, rolling times, rolling speed, etc. The rolling parameters set can be used to roll the battery pole piece coated with the ternary positive electrode material to obtain a battery pole piece that can reach a preset compaction density range, so the rolling parameters are not specifically limited.
[0053] In one embodiment, the quadratic polynomial fitting relationship curve of the deviation rate versus compaction density is y=ax 2 +bx+c; where 0<a, b<0, 0<c. Therefore, the true density instrument and mercury intrusion instrument method and their porosity test data can be converted equivalently according to the relationship with determined monotonicity, providing important reference value for subsequent indifferent lateral comparison.
[0054] In one embodiment, a, b and c simultaneously satisfy: 0<a<1, -2<b<0, 0<c<1. Thus, by further refining each coefficient in the quadratic polynomial, another test data converted using the curve can be closer to the actual detection situation, providing a more accurate basis for the conversion of the two.
[0055] In one embodiment, the fitting degree of the quadratic polynomial fitting relationship curve is greater than or equal to 90%. Thus, it can be more accurately and intuitively reflected that the quadratic polynomial established above can largely reflect the real relationship between the two, and the fitting relationship curve can be more in line with the actual detection situation and has a better fitting effect.
[0056] In one embodiment, the preset compaction density range is greater than or equal to 2.5 g / cm 3 , and less than or equal to 4g / cm 3 . As a result, it can meet most of the compaction density requirements of various performance batteries in the actual production process and has a wider range of applications.
[0057] In one embodiment, the ternary positive electrode material includes a ternary positive electrode material containing nickel. Exemplarily, the molar fraction of the nickel element in the ternary positive electrode material is greater than or equal to 0.6. Generally, if the molar fraction of nickel in the ternary positive electrode material reaches 0.6 or above, it can be considered as a high-nickel ternary positive electrode material, such as LiNi. 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2, etc. By acquiring and processing the porosity test data of high-nickel ternary cathode materials, the high energy density requirements of batteries for electric vehicles can be met.
[0058] In one embodiment, the number of battery pole pieces of the ternary positive electrode material is greater than or equal to 10. Thus, it is avoided that too few tests lead to large errors, affecting the accuracy of the curve and the reliability of the conclusion.
[0059] Example: The ternary positive electrode material NCM622 battery pole piece is compacted according to the preset density range of 2.5 to 4.5 g / cm 3 The corresponding rolling parameters are adjusted, and the battery electrode coated with the ternary positive electrode material is rolled to obtain an actual compaction density of 2.78 to 3.82 g / cm 3 11 battery pole pieces (numbered A to K). A mercury intrusion tester is used to test the porosity of each battery pole piece in turn, and multiple first porosity data are obtained by calculation. A true density tester is used to test the porosity of each battery pole piece in turn, and multiple second porosity data are obtained by calculation. Figure 3 ,in, Figure 3 The horizontal axis is the compacted density, unit: g / cm 3 , the vertical axis is porosity, unit: %; Figure 3 The porosity-mercury intrusion instrument data changes indicated by the golden lines are the first porosity data changes; Figure 3 The porosity-true density instrument data changes represented by the orange-yellow lines are the second porosity data changes.
[0060] Finally, after calculating the deviation rate, constructing the data scatter plot and linear fitting, we get the following Figure 4 The quadratic polynomial fitting relationship curve of the deviation rate and compaction density is shown. Figure 4 The horizontal axis is the compacted density, unit: g / cm 3 , the vertical axis is the deviation rate, unit: %.
[0061] The porosity calculation process is as follows:
[0062] (1) Calculate the surface density by dividing the mass of the battery electrode by the area of the battery electrode.
[0063] (2) The compaction density is calculated by dividing the mass of the battery electrode by the volume of the battery electrode after roller compaction.
[0064] (3) The true density is calculated by dividing the mass of the battery electrode by the actual volume of the battery electrode (excluding pores) obtained after the porosity test.
[0065] (4) The volume of the pores is obtained by subtracting the actual volume of the battery electrode sheet (excluding the pores) from the volume of the battery electrode sheet after roller compaction.
[0066] (5) The porosity is obtained by dividing the volume of the pores by the volume of the battery electrode after roller compaction.
[0067] Table 1
[0068]
[0069] It can be seen from Table 1 that the second porosity data measured by the true density meter is higher than the first porosity data measured by the mercury intrusion meter. Figure 3 It can be seen that the change trends of the first porosity data and the second porosity data are consistent with the change trends of the compaction density of the battery electrode.
[0070] After calculating the deviation rate of the second porosity data relative to the first porosity data, constructing a data scatter plot, and performing linear fitting, the following is obtained: Figure 4 The quadratic polynomial fitting relationship curve is shown in Figure 2. Figure 4 It can be seen that with the increase of the compaction density of the battery electrode, the deviation rate of the two also increases, and presents a linear change relationship of a quadratic polynomial, and the linear fitting degree is about 0.94.
[0071] According to this quadratic polynomial, a lateral indifferent comparative analysis of the porosity of NCM pole pieces with different compaction densities measured by a true density meter and a mercury intrusion meter can be achieved. For example: when it is necessary to use a true density meter to test the porosity of a battery pole piece with a certain actual compaction density, the porosity test data of the true density meter can be calculated according to the actual test results and the above-mentioned porosity calculation process. Then, the actual compaction density of the battery pole piece is substituted into the quadratic polynomial fitting relationship curve to calculate the deviation rate, and then the porosity test data of the true density meter is multiplied by the deviation rate to obtain the porosity test data of the mercury intrusion meter. In this way, only one true density meter test is required to obtain different porosity test result data of two different test instruments, which can avoid the situation where the porosity data cannot be compared due to the different test equipment possessed by suppliers and various battery factories.
[0072] It should be noted that the technical solutions or technical features described in the above embodiments can be combined or supplemented with each other without causing conflicts. The scope of protection of this application is not limited to the precise structures described in the above embodiments and shown in the drawings; all modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of this application should be included in the scope of protection of this application.
Claims
1. A method for acquiring and analyzing the porosity test data of a battery electrode sheet of a ternary positive electrode material, characterized in that: include: Using specific process parameters that affect the porosity of the battery pole piece of the ternary positive electrode material as reference variables, multiple battery pole pieces of the ternary positive electrode material are prepared; A mercury intrusion instrument is used to sequentially test the porosity of each of the battery pole pieces, and a plurality of first porosity data are obtained by calculation; a true density meter is used to sequentially test the porosity of each of the battery pole pieces, and a plurality of second porosity data are obtained by calculation; respectively calculating a deviation rate of one of the plurality of first porosity data and the plurality of second porosity data relative to the other; In the same coordinate system, a data scatter plot of the specific process parameter and a data scatter plot of the deviation rate are established, and linear fitting processing is performed on the two data scatter plots to obtain a quadratic polynomial fitting relationship curve about the variation of the deviation rate with the specific process parameter.
2. The method for obtaining and analyzing battery pole piece porosity test data according to claim 1, characterized in that: Before taking the specific process parameters that affect the porosity of the battery electrode sheet of the ternary cathode material as reference variables, it also includes: Using a single variable method to prepare multiple battery pole pieces of ternary positive electrode materials using multiple process parameters that affect the porosity of the battery pole piece, and using a mercury intrusion porosimeter and a true density meter to test the porosity of the battery pole pieces of the multiple ternary positive electrode materials, so as to calculate the mercury intrusion porosity test data and the true density meter porosity test data respectively; Establishing a variation trend curve between the porosity test data of the mercury intrusion instrument and each of the process parameters, and a variation trend curve between the porosity test data of the true density instrument and each of the process parameters; According to the two change trend curves, the process parameters that show monotonic changes with the porosity test data of the mercury intrusion instrument and the porosity test data of the true density instrument are obtained from all the process parameters as the specific process parameters.
3. The method for acquiring and analyzing battery pole piece porosity test data according to claim 2, characterized in that: All the process parameters include compaction density and at least one of the particle size of raw material particles, binder dosage, coating thickness, coating speed and roller pressure other than the compaction density.
4. The method for acquiring and analyzing battery pole piece porosity test data according to claim 1, characterized in that: The specific process parameters include compaction density; Taking the specific process parameters that affect the porosity of the battery electrode sheet of the ternary positive electrode material as reference variables, a plurality of battery electrode sheets of the ternary positive electrode material are prepared, including: The rolling parameters are set according to the preset compaction density range of the battery pole piece of the ternary positive electrode material, and after rolling with different rolling parameters, a plurality of battery pole pieces of the ternary positive electrode material with different compaction densities are obtained.
5. The method for acquiring and analyzing battery pole piece porosity test data according to claim 4, characterized in that: The quadratic polynomial fitting relationship curve of the deviation rate changing with the compaction density is y=ax 2 +bx+c; wherein, 0<a, b<0, 0<c.
6. The method for acquiring and analyzing battery pole piece porosity test data according to claim 5, characterized in that: The a, b and c simultaneously satisfy: 0<a<1, -2<b<0, 0<c<1.
7. The method for acquiring and analyzing battery pole piece porosity test data according to claim 5, characterized in that: The fitting degree of the quadratic polynomial fitting relationship curve is greater than or equal to 90%.
8. The method for acquiring and analyzing battery pole piece porosity test data according to claim 4, characterized in that: The preset compaction density range is greater than or equal to 2.5 g / cm 3 , and less than or equal to 4g / cm 3 .
9. The method for acquiring and analyzing battery pole piece porosity test data according to any one of claims 1 to 8, characterized in that: The ternary positive electrode material includes a ternary positive electrode material containing nickel element.
10. The method for acquiring and analyzing battery pole piece porosity test data according to any one of claims 1 to 8, characterized in that: The number of battery pole pieces of the ternary positive electrode material is greater than or equal to 10.
Citation Information
Cited By
Preparation method of secondary battery, secondary battery, energy storage system and electric equipment
CN120356904A